Improving Knowledge of Healthy Lifestyle Using WhatsApp Application and Health Screening of Productive Age Population in Pajimatan Hamlet, Imogiri, Bantul - Janatin Hastuti, S.Si, M.Kes, Ph.D; Neni Trilusiana Rahmawati (Journal of Community Empowerment for Health, 2023)
Introduction: The prevalence of obesity continuously increases, as are associated comorbidities and healthcare expenses. Early detection, intervention, and effective treatment of obesity are important to improve the quality of life and reduce costs. This Community Practice Program aimed to evaluate health status and provide education about the healthy lifestyle of people at productive ages in Pajimatan Hamlet, Imogiri, Bantul, Yogyakarta. Methods: Participants were 66 adults (26 men, 40 women) aged 19-64 years living in Pajimatan Hamlet. The program was held on November 2021. Education on a healthy lifestyle was done using social media via WhatsApp groups. Pre- and post-test were given to the participant before and after the education. Health screening measured height, weight, waist circumference (WC), blood pressure BP), and fasting blood glucose level. Obesity was determined using body mass index (BMI) and WC. Results: There were significant increases in healthy lifestyle knowledge scores before and after education in men (p= 0.017) and women (p< 0.001). Health screening indicated that men were significantly taller (p< 0.001) and heavier (p= 0.009) than women; however, there was no difference in BMI, WC, BP, and fasting blood glucose level (p> 0.05). There were no differences in the distribution of BMI obesity between men and women; however, women with central obesity were higher than men (70% women, 30% women, p= 0.021). Men having prehypertension were higher than women (46.2 vs. 15%); on the other hand, women with hypertension I and II seemed to be higher than men (p= 0.043). Type-2 diabetes was slightly greater in women (12.5%) than 7.7% in men. Conclusion: In conclusion, the Community Service Program found a high prevalence of obesity and hypertension in the population. Education on healthy lifestyle programs can help improve the target population’s knowledge.